Ultrasound-guided iliopsoas plane block combined with lateral femoral cutaneous nerve block for postoperative analgesia in hip arthroplasty: a retrospective case series - Jian Chen; Cong Liu; Meng-Lan Zhou; Hui-Wen Wang (Perioperative Medicine)
Abstract In recent years, iliopsoas plane block as a new type of regional nerve block technique has gradually gained attention; however, its actual effect on analgesia and motor function preservation in postoperative hip arthroplasty patients has not been fully verified. Because of this, we summarize the experience of 10 cases of successful application of iliopsoas plane block (IPB) combined with lateral femoral cutaneous nerve (LFCN) block for postoperative pain management after hip arthroplasty, to provide useful reference and inspiration for clinical practice.